GETTING RUSSIA RIGHT - Graham, Thomas E., Jr (A Council on Foreign Relations Book, Polity, 2023)
"With a practitioner's eye honed during decades of work on Russian affairs, Thomas Graham deftly traces the evolution of opposing ideas of national purpose that created an inherent tension in relations. Getting Russia Right identifies the blind spots that prevented Washington from seeing Russia as it really is and crafting a policy to advance American interests without provoking an aggressive Russian response. Distilling the Putin factor to reveal the contours of the Russia challenge facing the United States whenever he departs the scene, Graham lays out a compelling way to deal with it so that the United States can continue to advance its interests in a rapidly changing world." --